The functional motifs for nucleocytoplasmic shuttling of C-terminal fragment of c-Met - Chaudhary Shubhash Chandra (The Graduate School, Ajou University, 2015)
The C-terminal fragment of the c-Met receptor tyrosine kinase is present in the nuclei of various cells irrespective of ligand stimulation, but neither the specific amino acid motif nor the responsible nuclear localization signal (NLS) has not been previously reported. Here, we report that two histidine residues separated by a 10-amino-acid spacer (H1068-H1079) located in the juxtamembrane region of c-Met function as a putative novel NLS. Immunocytochemistry and cellular fractionation assays revealed that deletion of these sequences significantly abolished the nuclear translocation of c-Met in HeLa cells, as did substitution of the histidines with alanines. This substitution also decreased the nuclear translocation of the c-Met fragment and its association with importin β, the carrier protein. The putative NLS of c-Met is unique in that it relies on histidines, whose positive charge changes depending on pH, rather than the lysines or arginines, commonly found in classical bipartite NLSs, suggesting the possible ‘pH-dependency’ of this NLS. Indeed, decreasing the cytosolic pH either with nigericin, a Na+/H+ exchanger or low pH KRB (pH=6.5) buffer significantly increased the level of nuclear c-Met and the interaction of the c-Met fragment with importin β, indicating that low cytosolic pH itself enhanced nuclear translocation of cytosolic fragment of c-Met. Consistent with this, nigericin treatment also enhanced the nuclear accumulation of endogenous c-Met in HeLa cells. Moreover, replacement of histidines either with lysines or arginines abolished the “pH-dependency” at the same time. To the best of our knowledge, the putative aberrant bipartite NLS of c-Met seems to be the first example of what we call a “pH-dependent” NLS. Furthermore, we also report here a putative leucine-rich nuclear export signal (NES) in c-Met which plays a decisive role for nucleocytoplasmic shuttling of the receptor. Taken together, these results suggest that the shuttling of the C-terminal fragment of c-Met between the cytosol and nucleus appears to be due to the presence of both a putative NLS and an NES in the juxtamembrane region.
학위논문(박사)--아주대학교 일반대학원 :의생명과학과,2015. 2
Keywords: c-Met; proto-oncogene; monopartite; NLS